TEACHING TAHFIDZ IN THE TODDLER AND CHILD TAHFIDZ HOUSE (RUTABA) SIDOARJO - Tirandicha, Fajar; Rindanigsih, Ida (Antis-Publisher, 2024)
This study aims to enhance the teaching effectiveness of the tahfidz programme for toddlers at Rumah Tahfidz Balita dan Anak (RUTABA) Sidoarjo. The research employed a qualitative approach with a case study design, and data were collected through classroom observation, interviews, and document analysis. The findings revealed that increased teacher understanding is crucial for the success of memorising tahfidz among toddler students. The significance of the teacher's role in effective guidance and teaching is emphasised. Additionally, parental involvement is recognised as a crucial factor in improving the quality of memorisation and maintaining the spirit of memorisation of toddler tahfidz students. The use of technology was found to be highly beneficial in tahfidz learning, both in school and during murojaah at home. This indicates that integrating technology can enhance learning effectiveness. Factors such as teachers' professional development and rote memorisation were identified as being able to increase motivation and set an example in the tahfidz programme for students. This highlights the importance of skill development and ongoing support for educators. Continuous evaluation is a method of enhancing the quality of students' memorisation that is carried out regularly according to a schedule. This approach highlights the significance of continuous monitoring and assessment to improve the quality of learning. Therefore, this abstract demonstrates a comprehensive approach to teaching tahfidz to toddlers by emphasising the roles of teachers, parents, technology, professional development, and continuous evaluation.